Anita Blake, vampire hunter. The first death - Hamilton, Laurell K. (Marvel, 2008)
This tale is set before the first Anita Blake novel, Guilty pleasures, to reveal how Anita's career began. The handbook section includes a who's who with in-depth bios of Anita's friends, foes and supporting cast from the first Anita Blake novel.